LEGAL STANDING PERATURAN SEMA NO. 2 TAHUN 2023 DALAM POLEMIK ATURAN KAWIN BEDA AGAMA: Legal Standing Sema Regulation no. 2 of 2023 in the Polemic on the Rules for Marriage between Different Religions - Masyayih, Ali Akbar; Al Waris, Moh. Wahyu (UIN Kiai Haji Ahmad Sidiq Jember, 2024)
Interfaith marriage is currently still a hot topic of discussion among legal observers and the general public. This is very logical considering that Indonesia is a country that is diverse in beliefs, languages ??and religions. The aim of this research is to find out the legal standing or position of SEMA Number 2 of 2023. This research method is normative juridical. The approach used is a statutory regulation approach, namely an approach implemented based on new and/or current legislation in force as related positive law and a concept approach is an approach implemented based on the forms and concepts that can be obtained in opinions. scholarly opinions or legal doctrines relating to related legal issues. Data collection was carried out by means of literature study. The theory used is Gustav Radbruch's legal certainty. The research results show that SEMA No. 2 of 2023, which was initially hoped to be able to overcome the polemic regarding the regulation of interfaith marriages, however, it is still a long-standing controversy surrounding interfaith marriages. Abstak Perkawinan beda agama pada saat ini masih menjadi perbincangan hangat oleh para pengamat hukum serta khalayak umum. Hal ini sangat logis mengingat Indonesia adalah negara yang beragam dari kepercayaan, Bahasa dan agama. Tujuan penelitian ini yaitu mengetahui legal standing atau kedudukan SEMA Nomor 2 Tahun 2023. Metode penelitian ini ialah yuridis normatif. Pendekatan yang digunakan merupakan pendekatan peraturan perundang-undangan yakni pendekatan yang dilaksanakan berlandaskan pada Peraturan Perundang-Undangan baru dan atau sedang berlaku sebagai hukum positif yang terkait dan pendekatan konsep ialah pendekatan yang dilaksanakan dengan didasarkan pada bentuk-bentuk dan konsep yang dapat diperoleh dalam pendapat-pendapat sarjana atau doktrin-doktrin hukum yang berkaitan dengan persoalan hukum terkait. Pengumpulan data dilaksanakan dengan cara studi pustaka. Teori yang digunakan adalah kepastian hukum milik Gustav Radbruch. Hasil penelitian menunjukkan SEMA No. 2 Tahun 2023 yang pada awalnya diharapkan mampu mengatasi polemik peraturan kawin beda agama namun masih saja menjadi polemik kontroversi yang bekepanjanganseputar perkawinan beda agama.